Rancang Bangun Sistem Informasi Monitoring Perkembangan Anak Usia Dini Berbasis Web Metode Waterfall - Putria, Narti Eka; Hakim, Arif Rahman; Yulia, Yulia (Prosiding, 2024)
Yayasan Harapan Ibu RA. Insan Harapan is a religious foundation for early childhood education and has been established since 2016 with a building area of ​​400 m2. Yayasan Harapan Ibu RA. Insan Harapan still utilizes information technology to support various activities including having a WhatsApp group. In addition to using the WhatsApp group, each child is also given a liaison book whose function is to convey information to guardians, but the use of this liaison book is still ineffective because guardians often do not read it so that the child lags behind his friends, and to find out how the child is developing at school each guardian usually asks his teacher directly. The results of the child development monitoring report are given to guardians periodically every semester. Most schools still carry out monitoring manually, the form of reporting using books takes a long time both in terms of recording and searching for student data when needed. Another problem experienced by Yayasan Harapan Ibu RA. Insan Harapan is the absence of a media in the form of a website, in recording various data related to school information, recording educational institution activities, conveying information on child development in teaching and learning activities, updating student data and other related matters takes a long time. The purpose of this study is to design a web-based early childhood development monitoring information system using the waterfall method, to facilitate parents and teachers to have harmony in monitoring children's development and facilitate school academic activities. PHP is used to develop the website, and MySQL as a database server. UML (Unifield Modeling Language) to define requirements, create analysis and design, and describe architecture in object-based programming.